The Metatheoretical Study of the Tourism System of the Volgograd Region and the Study of Preferences of Consumers of Regional Tourism Products - Aleksandrovna Sizeneva, Lidiya; Vasilievich Dyachenko, Aleksandr; Leonidovna Kosulnikova, Tatyana (International Journal of Engineering and Technology, 2018)
The metatheoretical study of the tourism system of the Volgograd Region of the Russian Federation made it possible to determine the system characteristics of tourist relations of the region. Currently, an excursion type of tourism, in particular, war-historical and theological ones, is the main one in the region; this type is organized by two types of tourism products: tours (overnight) and excursions (without staying for the night). The focused interview with an expert group revealed the components and elements of the tourism product "excursion tour", which were grouped and listed in a questionnaire to assess the importance of each component and each element of the tourism product among consumers. 332 people divided into 6 age-sex groups took part in the survey. The survey results enable to form a methodology for the integrated assessment of regional tourism products: average estimates of the importance of each component and element of the tourism product for each group of respondents have been calculated; all the elements of the tourism product have been divided into two types (impression-forming and consumption-covering), to which essentially different evaluation scales are applicable.Â Â